(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The purpose of this paper is to develop a generalized model using Matlab/Simulink program to study the dynamic behavior of a three-phase induction motor. Dynamic models are used to better understand the behavior of an induction motor in both transient and steady-state conditions. The dq axis transformation theory is applied in the rotor reference frame to study the dynamics of the motor. A model has been developed using the Matlab/Simulink software for dynamic modeling of a 4-pole induction motor with a power of 0.75 kW, power factor cosφ=0.76, efficiency η=73%, rated current I1=2.05 A. The developed model is used for research the influence of changes in stator resistance, moment of inertia and load torque. The results show that the torque characteristic curve and rotor speed of an induction motor depend on the rotor resistance and moment of inertia. All differential voltages, currents and magnetic fluxes between the stationary stator and the moving rotor are also modeled.